PENGEMBANGAN MEDIA PERMAINAN LEGO BRICK UNTUK MEMBANTU MENINGKATKAN KEMAMPUAN KONGNITIF MATEMATIKA ANAK USIA 8 TAHUN - M. Abyadi; Sahrun Nisa, Ari Suriani (ADISAM PUBLISHER, 2025)
This study aims to facilitate the process of learning math multiplication operations, using Lego Brick game media can help and also improve students' learning ability in working on problems with the media. The research method used is literature review. The study method is a scientific method used to obtain data or information for predetermined purposes and interests. The results of this article can be concluded that developing game media in the form of lego bricks to help improve cognitive math skills of 8-year-old children is very effective for applying the media as learning because it uses concrete and real objects, can solve problems in learning multiplication operations easily, and is not boring.